(untitled) (Biological Sciences - PJSIR, 1997)
In a recent study [11, it was observed that aniline failed to exert its scavenging action in dibromomethane-aniline or dibromoethane-aniline mixtures due to the formation of crys- tals in the systems and the activities of electrodeposited radiobromines fell off sharply. The experiment with dibromomethane (DBM) in N,N-dimethylaniline (N,N- DMA) showed the same decreasing trend regarding the.elec- trode activities. Here, we present the results of our study on energetic bromine reactions in DBM -N,N-DMA mixtures by charge plate collection experiments and discuss the mecha- nism of stabilisation mode of sOmBr,sOBrand 82Brspecies in the system.